2014
DOI: 10.1051/0004-6361/201322714
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical uncertainties of the Type Ia supernova rate

Abstract: It is thought that Type Ia supernovae (SNe Ia) are explosions of carbon-oxygen white dwarfs (CO WDs). Two main evolutionary channels are proposed for the WD to reach the critical density required for a thermonuclear explosion: the single degenerate (SD) scenario, in which a CO WD accretes from a non-degenerate companion, and the double degenerate (DD) scenario, in which two CO WDs merge. However, it remains difficult to reproduce the observed SN Ia rate with these two scenarios. With a binary population synthe… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
326
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 271 publications
(346 citation statements)
references
References 118 publications
17
326
1
Order By: Relevance
“…These codes rely on precomputed grids of detailed stellar models and approximate treatments of the physical processes as described below. Despite the approximations, studies with this and similar codes based on the same philosophy have enabled insights into the many exotic phenomena resulting from lowand high-mass interacting binaries (e.g., recent work by Izzard et al 2004Izzard et al , 2006Izzard et al , 2009Ruiter et al 2009Ruiter et al , 2014Mennekens et al 2010;Abate et al 2013;de Mink et al 2013de Mink et al , 2014Fragos et al 2013;Vanbeveren et al 2013;Claeys et al 2014;Kochanek et al 2014;Mennekens & Vanbeveren 2014;Schneider et al 2014Schneider et al , 2015Toonen et al 2014).…”
Section: Methodsmentioning
confidence: 99%
“…These codes rely on precomputed grids of detailed stellar models and approximate treatments of the physical processes as described below. Despite the approximations, studies with this and similar codes based on the same philosophy have enabled insights into the many exotic phenomena resulting from lowand high-mass interacting binaries (e.g., recent work by Izzard et al 2004Izzard et al , 2006Izzard et al , 2009Ruiter et al 2009Ruiter et al , 2014Mennekens et al 2010;Abate et al 2013;de Mink et al 2013de Mink et al , 2014Fragos et al 2013;Vanbeveren et al 2013;Claeys et al 2014;Kochanek et al 2014;Mennekens & Vanbeveren 2014;Schneider et al 2014Schneider et al , 2015Toonen et al 2014).…”
Section: Methodsmentioning
confidence: 99%
“…For example, Ruiter et al (2013) found that a "violent merger" DD model predicts a t −1 power law shape for long delay SNe, but also includes a very prompt component that arises from a distinct subset of binary systems. A separate prompt channel for SN Ia explosions could also arise from a single degenerate pathway with a helium star donor (Wang et al 2009;Claeys et al 2014). …”
Section: Isolating the Prompt Sn Ia Fractionmentioning
confidence: 99%
“…In the case of TTMT the prescription from Claeys et al (2014) may overestimate the mass transfer rate. We therefore also ran our simulations with the original prescription, which underestimates the mass transfer rate.…”
Section: Calculating the Thermal Time-scale Mass Transfer Ratementioning
confidence: 99%